Rancang Bangun Sistem Keamanan Laser Berbasis Internet of Things Menggunakan Metode Prototyping dengan Peringatan Dini dan Bukti Visual Real-Time Untuk Mencegah Pencurian - Randikal Hikrenc Menono; Vilianty Rafida; Ahmad Fajri (Bulletin of Computer Science Research, 2026)
The rapid development of digital technology, particularly in the field of the Internet of Things (IoT), has brought significant changes to various aspects of human life, including security systems. Security is a crucial aspect for business owners, especially those operating in environments with a high risk of theft. This study aims to design and develop an IoT-based laser security prototype capable of providing real-time early warning notifications to users. The research employed the Prototyping method, which consists of communication, quick plan, modeling quick design, construction of prototype, and deployment and feedback stages. The system utilizes an ESP32-S3 Cam microcontroller as the main controller integrated with an LDR sensor and a SIM800L GSM module. The system operates by detecting interruptions in a laser beam caused by objects passing through the monitored area, which serve as intrusion triggers. When the laser beam is interrupted, the light intensity received by the LDR decreases significantly, prompting the microcontroller to automatically instruct the SIM800L module to place a phone call to the user. In addition, the ESP32-S3 Cam captures images of the monitored area and sends them through a Telegram bot as visual evidence. The testing results indicate that the system performs effectively, with an average response time of 8 seconds from intrusion detection to phone call notification. The success rate of phone call notifications reached 90%, while the visual evidence transmission through Telegram achieved a success rate of 100%. These results demonstrate that the system is capable of providing real-time alerts and visual information to users. The contribution of this research lies in the successful integration of intruder detection based on laser beam interruption, alarm notifications through telephone calls using the SIM800L module, and visual evidence transmission using the ESP32-S3 Cam and Telegram application into a single Internet of Things (IoT)-based security system capable of providing early warning notifications. When a laser beam interruption is detected, the system can automatically notify users through a phone call and send visual evidence in real time, thereby enhancing the effectiveness of remote security monitoring and response. However, the system performance is still affected by the stability of the GSM network used by the SIM800L module and is limited to detecting objects that interrupt the laser beam path. Therefore, the proposed system offers a smart, responsive, and cost-effective security solution that enables remote monitoring and supports theft prevention.